BUDAYA PESTA KHITAN BAGI ORANG MUSLIM DI KELURAHAN MOTOBOI KECIL - Paputungan, Ridwan (Universitas Sam Ratulangi, 2011)
Circumcision Feast Culture that was carrying out in a simple way previously, but recently aroundten years has changed by spending a huge amount of money, further more it is almost equal to a wedding feast. The purpose of this study is to assess the circumcision party culture, system of cooperation, and the response of muslim community in Motoboi Kecil Village toward circumcision party. The result showed that the circumcision party culture in the village of Motoboi Kecil has no different with the circumcision party culture in other area of Mongondow Bolaang.Â Circumcision feast here is the form of thanks giving prayer for their child being circumised. The system of cooperation that exist in the society which helpshape energy cooperation and cooperation in the form of social gathering. Community responses are not all involved in family assistance, which performans the show, but saw his social status in society. From this research it ca conclude that the circumcision feast culture for muslims in the village of Motobi Kecil do not experience changes and no different from other places in Bolaang Mongondow. It is suggested that the celebration should not to much spending money and religious value should be the first. Keywords : muslim, party culture, Motobai